Clinical manifestations and immune correlations in anti-centromere antibody-positive and anti-SSA/Ro antibody-positive primary Sjögren’s syndrome: A retrospective analysis - Songyan Zou; Riyi Zhang; Dongdong Yang; Xiaodong Li; Naixiang Huang; Fuyi Xie; Yinyu Mu (PLoS ONE, 2025)
Primary Sjögren’s syndrome (pSS) is an autoimmune disorder characterized by dry eyes and mouth, often with systemic involvement. This study aimed to investigate the clinical manifestations and laboratory features in pSS patients, particularly focusing on those with anti-centromere antibodies (ACA) and anti-SSA/Ro antibodies. We conducted a retrospective analysis of 152 patients diagnosed with pSS at Ningbo Medical Center Lihuili Hospital from 2018 to 2023, using the 2016 ACR/EULAR criteria. Additionally, 105 age- and sex-matched healthy controls were included to establish a comparative baseline for laboratory parameters. Clinical data were obtained from medical records, and patients were categorized into ACA-positive and SSA-positive groups based on their autoantibody profiles. Appropriate statistical analyses, including ANOVA, chi-square tests, correlation analysis, and multivariate regression analysis, were used to compare clinical and laboratory parameters in pSS patients. ACA-positive patients were significantly older and exhibited a higher prevalence of Raynaud’s phenomenon and left ventricular diastolic dysfunction, while SSA-positive patients presented with more marked hematological abnormalities. ACA-positive patients have a more prevalent occurrence of positive antinuclear antibodies (ANA) and anti-mitochondrial M2 antibodies (AMA-M2), as well as significantly higher levels of left ventricular end-diastolic diameter (LVEDD), IgM, and lactate dehydrogenase (LDH). In addition, SSA-positive patients exhibited elevated levels of globulins (GLB), IgG, IgA, and rheumatoid factor (RF), accompanied by decreased albumin (ALB) levels. ACA-positive patients had abnormal proportions of CD4+ and CD8+ T cells and had reduced counts of NK cells (CD16+CD56+), CD3+ T cells, and CD8+ T cells. Correlation and multivariate regression analyses revealed a significant association between NK cell and levels of IgG, IgM, GLB, and LDH. Furthermore, SSA-positive patients showed abnormal proportions of CD19+ B cells and NK cells, with reduced counts of CD3+ T cells (including CD4+ and CD8+ T cells) and NK cells. Correlation and multivariate regression analyses indicated a significant correlation between CD4+ T cell and levels of IgG, ALB, and GLB. Overall, T cell-mediated immunity plays a significant role in SSA-positive patients; NK cells are shown to be critically involved in the pathogenesis of ACA-positive pSS.